(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted in the Gezira Research Farm(GRF) during the Rainy seasons of 2007 and 2008 to determine the waterrequirements, optimum irrigation regime, forage yield and forage waterproductivities of Sorghum cv Wad Ahmed (Sorghum bicolor L.Monech),phillipesara (Vigna trilobata), clitoria (Clitoria ternatea L.) and lubia(Lablab purpureus L.) as affected by irrigation regimes. The studyinvolved 12 treatments arranged in split plot design replicated three timesand with three irrigation regimes viz every 7, 14 and 21 days(W1,W2 andW3) in the main plots and the four crops as sub plots. The resultsindicated that in both seasons the irrigation regimes did not significantlyaffect the dry matter yield of any crop and hence W3 was considered asoptimum for all crop. In W3 however Wad Ahmed, (means of twoseasons) was associated with the lowest water requirements, (3818m 3 /ha), highest dry matter yield/ha, (7.2t/ha) and highest waterproductivity, (1.89 kg/m 3 ). The three legumes seemed to have comparablewater requirements, but phillipesara (among the legumes) was associatedwith the highest DM yield, (5.4t/ha) and highest water productivity, (1.18kg/m 3 ). Irrigation every 21 days (W3) seemed to be optimum for eachcrop during the rainy season.